Efeitos do aquecimento com saltos ou sprints na potencialização do desempenho neuromuscular - MONTEIRO, Cristian Cunha (2019)
Physical abilities such as strength, speed and power are performance determinants, and their optimization in training or competition can be improved through adequate heating, in which the plyometric training models stand out. Another possible strategy of its use is based on the so-called post-activation potentiation (PAP) phenomenon. The objective of the present study was to evaluate the effects of PPA from different protocols involving repeated Sprints (SR) and / or vertical jumps (SV) in the tests of velocity and vertical impulsion in futsal college athletes. To that end, the participants were randomly and individually submitted to each experimental model for the induction of PPA and then the data collection of countermovement jump (CMJ), Squat Jump (SJ) and velocity in 10 (V10m) and 20 meters (V20m) immediately after each procedure, five minutes after and ten minutes after experimental treatment. After analyzing the distribution of the data by the Shapiro-Wilk test, the results are presented as mean and standard deviation, when statistical significance was identified, the differences were located through Bonferroni post-hoc. Analyzes and significance were established when p <0.05. In conclusion, there was an improvement of 11% of the performance of V10m and 6% in V20m preceded by SR protocol. However, there seems to be no effect for SV and SR + SV protocols in speed tests. For CMJ jump, no performance improvements were observed from the proposed protocols. However, in performing SR + SR there was a decrease in SJ performance, and there was no difference in the performance of the other protocols. It is suggested, therefore, that physical trainers and athletes can include warm-up protocols as SR at certain stages of a physical training program in which power development is the main objective.